Efektivitas Penerapan Acupressure terhadap Kualitas Hidup Pasien Selama Hemodialisis: Sistematik Review dan Meta-Analisis - Diyanto, Deni; Febryandy, Valentino; Irawan, Aprianto Guntur (Indonesian Journal of Nursing Sciences and Practice, 2023)
Background: quality of life is an individual's perception of his or her position in life in the context of culture, value systems, and its relationship to life goals, expectations, standards, and other related things.Objective: this study aims to determine the effect of Acupressure in improving the quality of life of hemodialysis patients.Methods: The research used in this study was systematic review and meta-analysis using the PICOT method, by searching through Pubmed, Embese, and Proquest databases, so that as many as 6 articles were obtained that discussed the effectiveness of Acupressure in improving the quality of hemodialysis patients.Results: studies showed that most of the studies revealed that there was an effect of acupressure on improving quality of life in patients with hemodialysis. Acupressure actions such as improving sleep quality, reducing the intensity of pain, depression and anxiety. In conclusion, this acupressure therapy can be useful in improving the quality of life experienced by hemodialysis patients.Clinical implications: The results of this study are an indication of the importance of nonpharmacological therapy in nursing intervention by providing acupresuree to improve the quality of life of patients with chronic kidney failure disease while undergoing hemodialysis and patients can independently intervene as an effort to prevent and self-manage at home so that the patient's quality of life is improved during treatment.Keywords: Acupresuree, Hemodialysis, Quality of Life